Evaluation of Six Preendoscopy Scoring Systems to Predict Outcomes for Older Adults with Upper Gastrointestinal Bleeding - Yajie Li; Qin Lu; Kexuan Wu; Xilong Ou (Gastroenterology Research and Practice)
Objectives. To compare the ability of six preendoscopic scoring systems (ABC, AIMS65, Glasgow Blatchford score (GBS), MAP(ASH), pRS, and T-score) to predict outcomes of upper gastrointestinal bleeding (UGIB) in older adults. Methods. This was a retrospective study of 602 older adults (age≥65) presenting with UGIB at Zhongda Hospital Southeast University from January 2015 to June 2021. Six scoring systems were used to analyze all patients. Results. ABC had the largest area under the curve (AUC) (0.833; 95% confidence interval (CI): 0.801–0.862) and was significantly higher than pRS 0.696 (95% CI: 0.658–0.733, p<0.01) and T-score 0.667 (95% CI: 0.628–0.704, p<0.01) in predicting mortality. MAP(ASH) (0.783; 95% CI: 0.748–0.815) performs the best in predicting intervention and was similar to GBS, T-score, ABC, and AIMS65. The AUCs for MAP(ASH) (0.732; 95% CI: 0.698–0.770), AIMS65 (0.711; 95% CI: 0.672–0.746), and ABC (0.718; 95% CI: 0.680–0.754) were fair for rebleeding, while those of GBS (0.662; 95% CI: 0.617–0.694), T-score (0.641; 95% CI: 0.606–0.684), and pRS (0.609; 95% CI: 0.569–0.648) were performed poorly. MAP(ASH) performs the best in predicting ICU admission (0.784; 95% CI: 0.749–0.816). All the five scores were significantly higher than pRS (p<0.05 for ABC, AIMS65 and T-score, p<0.01 for GBS and MAP). Conclusions. Mortality, intervention, rebleeding, and ICU admission in UGIB for older adults can be predicted well using MAP(ASH). ABC is the most accurate for predicting mortality. Except for rebleeding, GBS has an acceptable performance in predicting ICU admission, mortality, and intervention. AIMS65 and T-score performed moderately, and pRS may not be suitable for the target cohort.